Intralingual translation, cultural accessibility and the ethics of translation: The Volxbibel as a case study - Seel, Olaf (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2024)
This article deals with the ethics of intralingual translation and cultural accessibility. Based on the analysis of five characteristic text examples of the Volxbibel, a German intralingual translation of the Bible which makes excessive use of local adaptive strategies and whose central aim is to make the Scriptures accessible to youngsters, it will be shown that cultural accessibility can only be achieved if the ethical dimension of semiotic translational transfer is taken duly into account. Methodologically, the analysis will be based on a contrastive pragmatic analysis of the Volxbibel and its canonical counterpart, the Lutherbibel. The results of the analysis reveal that ethically grounded intralingual translation can only be achieved when transfer actions are oriented, not only towards the translational skopos and the target-text, but, at the same time, respect the source-text author’s intention(s) and the source-text’s ideological and socio-cultural background. Finally, on the grounds of these results, a slight adjustment of Zethsen’s and Hill-Madsen’s criterial definition of translation is proposed, by explicitly integrating therein the ethical dimension. This would contribute to a more precise delineation of both intralingual and interlingual translation.